Infection with hypervirulent Mycobacterium tuberculosis triggers emergency myelopoiesis but not trained immunity - Maceiras, Ana Raquel; Silvério, Diogo; Gonçalves, Rute; Cardoso, Marcos S.; Saraiva, Margarida (Frontiers in Immunology, 2023)
During infection, bone marrow (BM) hematopoiesis is reprogrammed towards myeloid cell production, a mechanism named emergency myelopoiesis. In addition to replenishing myeloid cells, emergency myelopoiesis has been linked to trained immunity, a process that allows enhanced innate immune responses to secondary challenges. Although hematopoietic alterations during tuberculosis (TB) have been described and Mycobacterium tuberculosis may colonize the BM, studies using the mouse model of infection and the laboratory reference strain M. tuberculosis H37Rv demonstrated limited emergency myelopoiesis and trained immunity. To further address this issue, we used an experimental model that mimics the human blood immune signature of TB. Aerosol infection of C57BL/6 mice with high doses of the hypervirulent M. tuberculosis isolate HN878 resulted in alterations to the BM compatible with the occurrence of emergency myelopoiesis. We found increased frequencies of lineage-Sca-1+cKit+ (LSK) cells and of the granulocyte/macrophage progenitor (GMP) population. At the mature cell level, we observed an increase of monocytes and neutrophils in the blood and lung, likely reflecting the increased BM myeloid output. Monocytes or monocyte-derived macrophages recovered from the BM of M. tuberculosis HN878-infected mice did not show signs of trained immunity, suggesting an uncoupling of emergency myelopoiesis and trained immunity. Surprisingly, M. tuberculosis HN878-induced emergency myelopoiesis was not fully dependent on IFNγ, as mice lacking this cytokine and infected under the same conditions as wild-type ones still presented BM alterations. These data expand our understanding of the immune response to M. tuberculosis and raise awareness for pathogen strain-imposed differences to host responses.